PENGARUH CURRENT RATIO, KEBIJAKAN DIVIDEN, LEVERAGE, DAN RETURN ON ASSETS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Wenny Wenny; Winda Winda; Wisnu Haris Munandar; Annisa Nauli Sinaga; Thomas Firdaus Hutahaen (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to analyze the factors that affect the company’s stock price in Indonesian capital market especially in Consumer Goods Industry Sector. The variables used in this study is Current Ratio, Dividend Policy, Leverage and Return on Assets. This study uses a quantitative approach with multiple linear regression analysis model. This study uses the period 2013-2016. The number of observations used in this study were 36 observations. The results showed that the variable Current Ratio, Dividend Policy, Leverage, Return on Assets has negative not significantly effect on stock price.